1994
DOI: 10.3354/meps110259
|View full text |Cite
|
Sign up to set email alerts
|

Grazer-mediated regeneration and assimilation of Fe, Zn and Mn from planktonic prey

Abstract: Experiments were performed to investigate grazer remineralization and assimilation of Fe, Zn and Mn from autotrophic and heterotrophic plankton prey. Metal isotope activity incorporated into planktonic prey was added to bottles containing crustacean zooplankton grazers, and distribution of the added metals into dissolved, fecal pellet and grazer fractions was monitored over time. At the end of a 9 to 10 h grazing period, concentrations of dissolved metal isotopes were approximately 3 to 7 times higher in bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
122
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 35 publications
10
122
0
Order By: Relevance
“…Our data suggest that protistan grazing may be an additional source of iron binding ligands in seawater, through the regeneration of iron from bacterial biomass. Similar theories have been suggested for metazoan grazing (Hutchins & Bruland 1994) and viral lysis of cells (Gobler et al 1997). The binding strength and bioavailability of the putative iron ligands produced in our model systems is unknown.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Our data suggest that protistan grazing may be an additional source of iron binding ligands in seawater, through the regeneration of iron from bacterial biomass. Similar theories have been suggested for metazoan grazing (Hutchins & Bruland 1994) and viral lysis of cells (Gobler et al 1997). The binding strength and bioavailability of the putative iron ligands produced in our model systems is unknown.…”
mentioning
confidence: 69%
“…A number of radiotracer studies have indicated that protistan grazers are capable of regenerating trace metals from ingested prey to the dissolved phase, and in some cases these regenerated trace metals have been shown to be available for biological uptake (Hutchins et al 1993, Hutchins & Bruland 1994, Twiss & Campbell 1995, Barbeau et al 1996, Twiss et al 1996, Chase & Price 1997. Ecological studies indicate that, in HNLC (high nitrate, low chlorophyll) regions, recycling of iron as mediated by microzooplankton grazers may be a key parameter in ecosystem productivity (Landry et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoplankton mortality and iron regeneration-In HNLC regions new sources of iron have been suggested (Hutchins et al 1995) to support only 20% or less of the primary productivity, and, thus, iron regeneration is likely to be a key parameter in ecosystem productivity (Landry et al 1997). It has been calculated that regenerated iron could supply as much as 90% of the demand in limited areas (Poorvin et al 2004), and both microzooplankton grazing (Hutchins and Bruland 1994) and viral lysis (Gobler et al 1997;Poorvin et al 2004) of phytoplankton have been shown to be sources of regenerated iron.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is now known to control phytoplankton stocks in HNLC regions [Boyd et differing abilities to obtain iron bound to siderophores and porphyrin complexes [Hutchins et al, 1999]. Particulate iron is also transformed into dissolved iron by protozoan [Barbeau et al, 1996] or zooplankton grazing [Hutchins and Bruland, 1994]. Interactions between microbial processes and iron chemistry appear to determine the biogeochemistry of iron in oceanic waters [Geider, 1999;Kirchman, 1996 …”
Section: Introductionmentioning
confidence: 99%